Antenatal Diagnosis of Intrauterine Infection With Coxsackievirus B3 Associated With Live Birth - Annie Ouellet; Rebecca Sherlock; Baldwin Toye; Karen Fung Kee Fung (Hindawi Limited, 2004)
Background: Prior reported cases of stillbirth and neonates infected with enteroviruses suggest transplacental infection. We present a case of fetal infection with coxsackievirus B3, diagnosed antenatally and resulting in live birth.